A Water‐Soluble, NIR‐Absorbing Quaterrylenediimide Chromophore for Photoacoustic Imaging and Efficient Photothermal Cancer Therapy. Issue 6 (9th January 2019) - Liu, Chang; Zhang, Shaobo; Li, Jianhao; Wei, Jie; Müllen, Klaus; Yin, Meizhen
Abstract: Precision phototheranostics, including photoacoustic imaging and photothermal therapy, requires stable photothermal agents. Developing such agents with high stability and high photothermal conversion efficiency (PTCE) remains a considerable challenge. Herein, we introduce a new photothermal agent based on water‐soluble quaterrylenediimide (QDI) that can self‐assemble into nanoparticles (QDI‐NPs) in aqueous solution. Incorporating polyethylene glycol (PEG) into the QDI core significantly enhances both physiological stability and biocompatibility of QDI‐NPs. The highly photostable QDI‐NPs offer advantages including intense absorption in the near‐infrared (NIR) and high PTCE of up to 64.7±4 %. This is higher than that of commercial indocyanine green (ICG). Their small size (ca. 10 nm) enables sustained retention in deep tumor sites and also proper clearance from the body. QDI‐NPs allow high‐resolution photoacoustic imaging and efficient 808 nm laser‐triggered photothermal therapy of cancer in vivo. Abstract : Red light white heat : The poly(ethylene glycol)‐functionalized quaterrylenediimide (QDI) can self‐assemble into QDI‐nanoparticles (QDI‐NPs) with sizes of approximately 10 nm in aqueous solution. QDI‐NPs exhibit high‐resolution photoacoustic imaging and efficient photothermal cancer therapy at 808 nm NIR laser irradiation.